Developmental bias in horned dung beetles and its contributions to innovation, adaptation, and resilience. Issue 1 (2nd September 2019) - Hu, Yonggang; Linz, David M.; Parker, Erik S.; Schwab, Daniel B.; Casasa, Sofia; Macagno, Anna L. M.; Moczek, Armin P.
Abstract: Developmental processes transduce diverse influences during phenotype formation, thereby biasing and structuring amount and type of phenotypic variation available for evolutionary processes to act on. The causes, extent, and consequences of this bias are subject to significant debate. Here we explore the role of developmental bias in contributing to organisms' ability to innovate, to adapt to novel or stressful conditions, and to generate well integrated, resilient phenotypes in the face of perturbations. We focus our inquiry on one taxon, the horned dung beetle genus Onthophagus, and review the role developmental bias might play across several levels of biological organization: (a) gene regulatory networks that pattern specific body regions; (b) plastic developmental mechanisms that coordinate body wide responses to changing environments and; (c) developmental symbioses and niche construction that enable organisms to build teams and to actively modify their own selective environments. We posit that across all these levels developmental bias shapes the way living systems innovate, adapt, and withstand stress, in ways that can alternately limit, bias, or facilitate developmental evolution. We conclude that the structuring contribution of developmental bias in evolution deserves further study to better understand why and how developmental evolution unfolds the way it does. Abstract : Case studies on Onthophagus beetles on the role of developmental bias in evolution through (i) gene networks, (ii) environment sensitive development, and (iii) symbioses. Research Highlights: The significance of developmental bias (DB) is much debated. We focus our inquiry on one taxon, the horned dung beetle genus Onthophagus, and review the role of DB in the evolution of novelty, adaptation, and resilience. We posit that across levels of organization DB shapes the way living systems innovate, adapt, and withstand stress. Such biases may alternately limit or facilitate developmental evolution. We conclude that the structuring contribution of developmental bias in evolution deserves further study.